Interests of developing countries and the consensus principles of the WTO world trade organization (2012)
In this Article, I have attempted an examination of the process of decision-making in the WTO. This consideration was provoked by the attribution of the Doha Round Negotiations impasse to the way the WTO makes decision in addition with the spate of criticisms against the WTO and the multilateral Trade Regime. I have attempted to answer the question whether the problem with Doha Round Negotiations lies in the way and manner the multilateral decision is made. I consider the alternatives proposed by scholars to replace consensus and the principle of Single Undertaking. I am not persuaded that the adoption of any of the alternative is the lasting solution to the problem of the WTO. A change of decision-making process of the WTO particularly a replacement of consensus rule and the principle of Single Undertaking is not an antidote to the problem of WTO. The emerging issue in the multilateral trade is that of development particularly in the developing and least developed countries. Economic growth of multilateral trade may not mean the same thing as development but how the negative impacts of global trade could be cushioned is the challenge that could bring lasting solution to the problem of the organization.